The relationship between maximal mouth opening agd age, height and weight in Nigerians. - O. O. Dosumu; N. M. Ibeabuchi; J. T. Arotiba; G. T. Arotiba (Nigerian Dental Association, 2008)
Objective: To establish the range of maximal mouth opening in Nigerians and explore it's relationship with age, height and weight. Methods: The interincisal distance in five hundred and one randomly selected healthy Nigerians between the ages of 17 and 69 years was measured using a disposable paper bite gauge. The iid measurements were taken with the subjects standing erect (basic head position) and with the head supported by the wall which had been marked for the height measurements. During both height and iid measurements the head was positioned such that the Frankfurt plane was parallel to the floor. The weight of the subjects was measured with a digital scale. Results: Majority (66.3%) of the subjects were in the 3 decade of life (21 30 years). The average Maximal mouth opening (iid) in males was significantly higher than that of females (54.19mm SD 6.73 versus 48.96mm SD 6.36; P < 0.001). The maximal mouth opening increased with increasing age, height and weight in both genders.  Conclusion: The normal range of maximal mouth opening (iid) in Nigerians was similar to those reported in Swedish, Greek, Nepalese and Japanese populations. Further investigations with larger sample and the use of more advanced instruments (e.g. the opto-electric jaw movement recording system) is highly recommended.